Humanizing the Classroom: Humanistic Education for Post-Disaster Learning Recovery in Madrasah of Central Sulawesi - Fakhrurrozi, Hatta; Dimyathi, M. Afifudin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2025)
This study aims to describe the implementation of a humanistic education model in a post-disaster schools, following the earthquake, tsunami, and liquefaction in Palu, Central Sulawesi, and focusing on learning strategies that place students at the center of the educational process, The objects of this study were two schools: MI AlKhairaat Lere and SDI Al Akbar Petobo. A qualitative approach was employed, with data collected through observation, in-depth interviews, and document analysis. Data were analyzed thematically through the stages of data reduction, data presentation, and conclusion drawing. The findings revealed six main points: (1) teachers implemented student-centered learning while taking into account students’ psychological conditions in the aftermath of the disaster; (2) learning methods were participatory and collaborative; (3) strengthening the values of empathy and solidarity was an integral part of the learning process; (4) curriculum flexibility was applied to accommodate students’ needs and limitations; (5) parents and communities were actively involved in supporting the learning process; and (6) a safe, comfortable, and motivating learning environment was established. The study concludes that applying a humanistic education model in post-disaster contexts is effective in restoring students’ learning motivation and rebuilding positive social interactions within schools. These findings are consistent with the principles of student-centered learning, active learning, and humanizing the classroom, while also contributing to the development of humanitarian-based educational strategies in times of crisis.